THE NEXUS BETWEEN HYBRID WARFARE AND CONTEMPORARY TERRORISM - Đorđević, Marko; Miljković, Milan (The Policy of National Security, 2025)
The paper's topic is to examine the depth of the connection between terrorism and hybrid warfare. Regardless of the current disagreements among theorists as to whether 'hybrid war' is a modern form of warfare or an 'old phenomenon in a new guise,' the fact is that this phenomenon involves the application of various elements and components of hard and soft power, through various non-violent and violent content, which certainly includes terrorism, to destabilize the legal order, cultural and value foundations of the attacked state and society. Considering that previous research has considered terrorism only at the level of actors in hybrid warfare and taking into account the complexity of the effects that terrorist activity has on the state and society to which it is applied, there is a need for a deeper examination of the place and role of this form of political violence in hybrid warfare. In this regard, the research question of this article relates to the connection between these two phenomena, not only considering the actors but also the dimensions and phases of the conduct of hybrid warfare. Hybrid warfare seeks out a state's weaknesses in the political, military, economic, social, infrastructure, information, and other domains and conducts activities within these dimensions using appropriate actors and tools. Terrorism, due to its complex nature and wide-ranging effects, is a suitable activity carried out by the state. Non-state actors of hybrid warfare, applying it with an adequate degree of escalation in the phases of preparation, destabilization, and coercion as the final phase, attacking critical infrastructure and other facilities with which they threaten the national economy, carrying out operations as proxy forces, exploiting socio-cultural divisions in societies, inserting themselves into migrant flows, placing and spreading specific messages and proclamations in the media, the effects of which spill over into various spheres of the attacked state. Through which forms of manifestation and through which dimensions of conducting hybrid warfare terrorism will be applied will depend on a multitude of different circumstances. It is important to emphasize that this phenomenon cannot be considered hybrid warfare without synchronization with other hybrid content, primarily psychological propaganda, information actions, and economic and political pressures. Only in synchronization with other hybrid content does terrorism achieve its goal, which is reflected in the weakening of defense capacities, the financial exhaustion of the country, and the creation of a social crisis in society, i.e., as part of preparatory operations for upcoming armed operations of a conventional nature. Ultimately, it can be concluded that there is a deeper connection between these two phenomena, not only through the well-known position that terrorist organizations can be one of the actors of hybrid warfare and that there is a possibility of common goals with other actors, but that a more profound connection is achieved through numerous dimensions and phases of conducting hybrid warfare.
Keywords: terrorism; hybrid warfare; actors; dimensions; implementation phases